Home Range Estimation and Food Plants Preference of Presbytiscomata at Situ Patengan Nature Reserve - Widiana, Ana; Januari, R. Robbi; Hasby, Rizal Maulana; Yuliawati, Astri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Surili (Presbytis comata) is one of endemic primates of West Java whose existence is protected. The purpose of the research was to determine the estimated home range and the preferences of food plant of P. comata at Situ Patengan Nature Reserve, West Java. The home range was determined by the minimum convex polygon method by connecting the coordinates of the outermost entire outer area groups. Focal animal sampling and Ad-libitum methods were applied to obtain data of food preferences in details. The result showed that home range of several P. comata groupsat Situ Patengan Nature Reserve were varied. The home range of group A, B, C, and D were covering 3.52 Ha, 4.43 Ha, 3.76 Ha, and 3.14 Ha respectively, while the solitary individual has a home range covering 2.64 Ha. There were 27 species from 16 families of plants that was directly consumed by P. comata. P. comata more often consumed Castanopsis javanica (10.07%), C. argentea (9.35%), C. tungurut (7.91%), Sloneasigun (7.91%), and Quercus sp (7.19%). This data can be useful as a reference in P. Comata population and habitat management especially in the area of Situ Patengan.